2021
DOI: 10.11648/j.ijepe.20211002.11
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Liquid Film Spreading on Tip of Spray Injector

Abstract: The behaviors of fuel films adhering to the tip of a fuel injector for automotive gasoline direct-injection engines was simulated by the computational fluid dynamics. Liquid film adhering to the tip of the fuel injector is a source of carbon deposits; the film spreads on the surfaces of the tip and remains there under certain wetting conditions. The deposit build-up can clog the injector nozzles, which can alter the spray pattern, furthermore, deposits on the tips of injectors are a source of particulate matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recently, there are investigations that simulate the tip-wetting phenomenon via computational fluid dynamic approaches. For instance, Ishii et al 17 used a hybrid cubic interpolated propagation and moving particle semi-implicit model to simulate fuel adhesion on injector tips, and they found that the floating droplets might be pulled to the tip and induce tip wetting. Fischer 18 performed a systematic tip-wetting study with both simulation approaches and experimental validations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are investigations that simulate the tip-wetting phenomenon via computational fluid dynamic approaches. For instance, Ishii et al 17 used a hybrid cubic interpolated propagation and moving particle semi-implicit model to simulate fuel adhesion on injector tips, and they found that the floating droplets might be pulled to the tip and induce tip wetting. Fischer 18 performed a systematic tip-wetting study with both simulation approaches and experimental validations.…”
Section: Introductionmentioning
confidence: 99%